Dried Apple Pie on the Chisholm Trail - Jane P. Marshall (Symphony in the Flint Hills, 2017)
Cowboys on the trail lived on such a steady diet of beans, sowbelly, biscuits, Arbuckle coffee, and dried apples that they told jokes and sang ditties like this one. Camp cooks did their best to vary three meals a day for the three-month trip up the Chisholm Trail from Texas to Kansas. For dessert there was pie made with “doctored up” dried apples.
Keywords: cowboy diet; recipes; 19th century; cattle drives